Sekolah Menengah Kesenian: Cipta Karakter Pelestari Budaya di Sumatera Barat - Sri Haryati Putri (Universitas Negeri Padang, 2019)
This study aims to delve deeper into how the role of art in traditional culture can be used as character building for the next generation of the nation. The art school which is specialized in Vocational High Schools (SMK), offers expertise programs to junior high school graduates who are interested in exploring and learning traditional arts and culture. The presence of art-based formal schools, of course, can have a positive impact on the younger generation to maintain and preserve the art of traditional culture as forming a moral character, as well as the emergence of a sense of love for their own culture. Usually Vocational Schools are very identical with technical schools, machinery, and other fields of technology, but art Vocational Schools in West Sumatra, especially the city of Padang, offer different skills than vocational education in general, namely traditional arts. This is evidenced by the presence of Vocational High School 4, Vocational High School 8 and Padang Vocational High School 7, which are art vocational schools in West Sumatra, especially in Padang which make traditional arts and crafts of Minangkabau culture a skill program developed by their students. This school is maintained and is the pride of the people of Padang City.